MAGNETIC ABRASIVE FINISHING - Vishwanath Patil; Prof. Jaydeep Ashtekar (International Journal of Innovations in Engineering Research and Technology, 2021)
Magnetic abrasive finishing is a machining process where the tooling allowance is remove by media with both magnetic and abrasive properties, with a magnetic field acting as a binder of a grain. Such machining falls into the category of erosion by abrasive suspension and lend itself to the finishing of any type of surface. The possibility of finishing complex surfaces is a special benefit of this machining. Magnetic abrasive finishing process is most suitable for obtaining quality finish on metallic and non-metallic surfaces. Magnetic abrasive finishing used for complicated product finishing & Roughness and tolerance band achieved that is difficult using conventional machine process. The product dimensional requirement easily possible with taking trial with MAF parameters.